الآثار الاجتماعية لحرمان المرأة من الميراث: دراسة حالة على النساء المحرومات من الإرث بمدينة توكرة - حسين مريم فرج مختار (Scientific Journal of University of Benghazi, 2023)
The aim of this study is to acknowledge the Causes and effects that have got women to be deprived of their inheritance right in Tucra country; and this study has been conducted through the following questions; Have they got deprived of all their inheritance right or just part of it? And what are the causes and effects of this deprivation? The descriptive method has been used to include the women who deprived of their right in Tucra country: as the non-random sample was used especially the snowball one, which estimated at 30 cases of the study. The way for collecting data was through open individual interviews and observations. Besides the women who told their stories, I have come up with these consequences: depriving women of their right that's related to land and houses. The superiority of males over females therefore. And the must for sisters to give up their right in family house for their youngest brother. Some women have got a part of that heritage just to be satisfied but they are not. Dominating the oldest brother over heritage, behaving with it freely, delaying giving rights and breaking promises, furthermore, violating whom asking for it. The consequences resulting from these causes such as. : breaking ties of kinship between brothers. Twenty of these cases were fully deprived, while seventeen cases were not satisfied about the illegal part of their right.